ANALYSIS OF STOCK PORTFOLIO PERFORMANCE USING THE SHARPE, TREYNOR AND JENSEN METHODS: (Study on stocks included in the Jakarta Islamic Index 70 on the Indonesia Stock Exchange for the period 2019-2022) - Andi Marwah; Anwar; Anwar Ramli; Nurman; Andi Mustika Amin (Transpublika Publisher, 2023)
This study aims to find out whether using the single index method will produce an optimal portfolio of Jakarta Islamic Index 70 (JII70) stocks listed on the IDX for the 2019-2022 period and continue to assess its performance using the Sharpe Ratio, Treynor and Jensen methods to find out the best method in assessing the performance of stock portfolios formed in a period. The selection of this research sample was used based on purposive random sampling technique. This study used the One Way of Variance by Rank Kruskal-Wallis different test. In this study, the Sharpe, Treynor, and Jensen values were standardized through the Z-score transformation (standardized) followed by the Mean Rank difference test between treatments. The test results using the Kruskal-Wallis test were obtained with a probability of 0.000. It is known that the probability of testing ≤ 0.05. These results indicate that there are significant differences between the tests with the Sharpe, Treynor, and Jensen methods. Thus, the null hypothesis H0 in this study was rejected. The test results between the three treatment differences in mean rank, showed no significant difference between each treatment because Jensen had the lowest difference in mean rank to Sharpe and Treynor. Jensen's method has a mean difference the lowest rank against Sharpe and Treynor, meaning that Jensen is the most consistent with indifference. Based on the results of the issuer's Jensen method analysis.